SUPPORT OF ENTREPRENEURSHIP AS THE BASIS OF INNOVATIVE DEVELOPMENT OF THE ECONOMY OF KAZAKHSTAN - Z.A. Baymagambetova; A.S. Doshan; E.S. Baitilenova; Zh.A. Nazikova; I.K. Suleimenova (Academic Journal of Physical and Chemical Sciences, 2019)
The support of entrepreneurship, according to the authors, is the basis of innovative development of the economy of Kazakhstan. An innovative vector of development is an objective necessity for Kazakhstan. Since, in the opposite case, Kazakhstan is influenced by such circumstances as a lag in the technological plan, the presence of national advantages of the resource type (territory and minerals), the lack of competitiveness of a domestic product can reduce its economic security. Thus, the prospect of innovative development is considered as a long-term direction of the structural policy in the field of science and business, and to ensure the overflow of investments in innovation.